Komunikasi Lingkungan Balai Besar Konservasi Sumber Daya Alam (BBKSDA) Riau Dalam Mengembangkan Ekowisata Di Taman Wisata Alam Buluh Cina Kabupaten Kampar - Rasina, Siti; Firdaus, Muhammad (Lembaga Dongan Dosen, 2025)
One of the conserved conservation forests is the Buluh Cina Nature Tourism Park by conducting environmental communication through an ecotourism development program to educate the public about the importance of maintaining forest areas and minimizing environmental damage caused by the community. The purpose of this study was to analyze environmental communication planning, analyze the implementation of environmental communication and analyze the evaluation of environmental communication by the Riau Natural Resources Conservation Center (BBKSDA) in developing ecotourism in the Buluh Cina Nature Tourism Park, Kampar Regency. This study uses a descriptive qualitative method. The number of informants was 6 people according to the criteria determined purposively. The data analysis technique in this study used the Miles and Huberman Model and the data validity checking technique was triangulation. The results of this study indicate that environmental communication carried out by BBKSDA in implementing environmental damage prevention requires communication planning consisting of analyzing problems, analyzing audiences, formulating objectives, developing messages, and planning media production. The implementation is socialization actions, monitoring areas and media use and evaluation is carried out using a monthly reporting application, related to development progress and updating current conditions related to achieving targets from the planning that has been made.